2018
DOI: 10.18245/ijaet.438048
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Prediction of Performance and Emission in an SI Engine Using Alternative Fuel with Artificial Neural Network

Abstract: In this study, the effect of using pure ethanol in different operating conditions of a spark ignition engine was experimentally investigated, and a backpropagation artificial neural network (ANN) model was developed to estimate the engine performance and exhaust emissions. For this purpose, the spark ignition (SI) engine having a compression ratio (CR) of 8.5:1, a single cylinder and air-cooled was used in the engine tests experiments, and the ANN model was created with using the C# programming language. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Ye et al (2018) have used neural networks to predict carbon emissions in the construction industry, where the economic development and improvement of standards might significantly impact carbon dioxide emissions in the future [11]. Balki et al (2018) have adopted backpropagation artificial neural networks to develop models that can estimate engine performance and exhaust emissions, finding that carbon emissions of ethanol vehicles are 6% lower than gasoline ones [12]. Liu et al (2017) have combined the chaos theory with the Backpropagation Neural Network (BPNN) to fit and predict carbon emission time series without considering other factors, proposing a method that is easier and more accurate than other prediction methods [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al (2018) have used neural networks to predict carbon emissions in the construction industry, where the economic development and improvement of standards might significantly impact carbon dioxide emissions in the future [11]. Balki et al (2018) have adopted backpropagation artificial neural networks to develop models that can estimate engine performance and exhaust emissions, finding that carbon emissions of ethanol vehicles are 6% lower than gasoline ones [12]. Liu et al (2017) have combined the chaos theory with the Backpropagation Neural Network (BPNN) to fit and predict carbon emission time series without considering other factors, proposing a method that is easier and more accurate than other prediction methods [13].…”
Section: Introductionmentioning
confidence: 99%
“…Balki et al, in their study, have used pure ethanol as fuel, and compared torque, bsfc, HC and CO2 values with that of gasoline. They reported that with using of gasoline as fuel, max torque was 11.1 Nm, min bsfc was 278.8 g/kWh, max HC emission was 196 ppm, max CO2 was 13.7%, on the other hand, with pure ethanol, max torque was 11.41 Nm, min bsfc was 453.7 g/kWh, max HC emission was 115 ppm, max CO2 was 13.2% [19].…”
Section: Introductionmentioning
confidence: 99%
“…Balki et al (2018) used back-propagation artificial neural networks to develop models that can estimate engine performance and exhaust emissions. It was found that the carbon emissions of ethanol vehicles were reduced by 6% compared to gasoline vehicles [12]. Liu et al (2017) used chaos theory combined with BP (Back Propagation) neural network to fit and predict carbon emission time series without considering other factors.…”
Section: Introductionmentioning
confidence: 99%